2013
DOI: 10.1063/1.4773339
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary light circulation and concentration of s- and p-polarized phase resonances

Abstract: Both s-polarized and p-polarized phase resonances in one-dimensionally compound transmission gratings are analyzed, modeled, and measured. We demonstrate that s-polarized phase resonances occur with similar characteristics of p-polarized phase resonances, with narrow bandwidths, high Q values, and highly amplified fields. The phase difference of π radian between the fields in the coupled cavities produces light circulation and an inversion of the transmissivity/opacity of the structure. The dependencies of ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…theoretically showed that PRs in low loss 2-groove CTGs can provide arbitrarily high field enhancement of the incident beam (limited only by the optical loss in the materials and fabrication tolerances) and electromagnetic filtering and channeling capabilities that may be useful for corrugated surface antennas. Also, the reader is referred to [18] that describes the design, fabrication and characterization of two single layer grating structures that support either s or p-polarized PRs; the experimental results matched the numerically modeled results as well as the predictions of the analytical model developed in [20].…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…theoretically showed that PRs in low loss 2-groove CTGs can provide arbitrarily high field enhancement of the incident beam (limited only by the optical loss in the materials and fabrication tolerances) and electromagnetic filtering and channeling capabilities that may be useful for corrugated surface antennas. Also, the reader is referred to [18] that describes the design, fabrication and characterization of two single layer grating structures that support either s or p-polarized PRs; the experimental results matched the numerically modeled results as well as the predictions of the analytical model developed in [20].…”
mentioning
confidence: 69%
“…There also is a Rayleigh anomaly due to the onset of far-field diffraction modes at 15 GHz. Also, there is a PR at 9.955 GHz exhibiting all the typical features of PRs (e.g., Fano resonance type of lineshape, flipping of the transmittivity/opacity, and light circulation) that have been extensively discussed in past works [18,20,21].…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This phenomenon is reminiscent of previously reported observations of negative power flow in periodic arrays of compound apertures. 23 However, our work here differs in that we consider aperiodic structures.…”
Section: Fig 1 Geometry Of the Proposed Subwavelength Spectral Lighmentioning
confidence: 99%
“…Composite engineered surfaces of various forms have been researched for years in many different technology fields (e.g., microwave, RF, optical) for applications that include electromagnetic (EM) radiation filtering to determine the polarization state and/or wavelength of an incident beam, or to perform beam steering, light harvesting, and light concentrating [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. This field has received increased attention recently because of the development of surface structures, composed of optically resonant metal structures (i.e., antennas) that operate in the infrared and visible spectral regions [20].…”
Section: Introductionmentioning
confidence: 99%